Neglected issues in road crashes in sub-sahara Africa: the example of Nigeria (2011)
Road crash is a global problem. It is more serious in Sub-Sahara Africa, especially in Nigeria because road transport account for more than 80% of the total traffic and road safety measures are poorly developed. Road traffic crashes in Nigeria have claimed many lives and rendered several people permanently injured. In spite of the wasted human resources and debilitating effect of road crashes on the socio-economic development of the country, some efforts which would have reversed the trend and lessened this burden are either neglected or ignored. These -include among others, training of drivers in the use of first aid technique, building of road side clinics, insurance and. compensation, Road Safety Fund as well as under- reporting of the magnitude and significance of road crash figures. The paper calls for the use of computer technology in the collation and analysis of road crash statistics, training of commercial drivers in First Aid techniques and the establishment of Nigerian Road Safety Emergency Service as well as Road Safety Fund. It must however be backed up with strong political will from the government and devoid of corruption. This is expected to bring about reduction in road carnage on Nigerian roads as well as ameliorating the socio-economic burden of road crash victims.